Decarbonisation of urban freight transport using electric vehicles and opportunity charging - Teoh, Tharsis (2018)
The high costs of using electric vehicles (EVs) is hindering wide-spread adoption of an EV-centric decarbonisation strategy for urban freight transport. Four opportunity charging (OC) strategies—during breaks and shift changes, during loading activity, during unloading activity, or while driving on highways—are evaluated towards reducing EV costs. The study investigates the effect of OC on the lifecycle costs and carbon dioxide emissions of four cases of different urban freight transport operations. Using a parametric vehicle model, the weight and battery capacity of operationally suitable fleets were calculated for ten scenarios (i.e., one diesel vehicle scenario, two EV scenarios without OC, and seven EV scenarios with four OC strategies and two charging technology types). A linearized energy consumption model sensitive to vehicle load was used to calculate the fuel and energy used by fleets for the transport operations. OC was found to significantly reduce lifecycle costs, and without any strong negative influence on carbon dioxide emissions. Other strong influences on lifecycle costs are the use of inductive technology, extension of service lifetime, and reduction of battery price. Other strong influences on carbon dioxide emissions are the use of inductive technology and the emissions factors of electricity production.